"At the point of confluence of sociology and Indology": Louis Dumont’s postulate reconsidered: - Michaels, Axel (Contributions to Indian sociology, 2020)
In this article, I aim to show how Louis Dumont’s famous claim that ‘the condition for a sound development of Sociology of India is found in the establishment of the proper relation between it and classical Indology’ has become obsolete and was from the beginning a problematic postulate. I first develop the historical background of the denigration of anthropological approaches in India against the rise of an idealising Indology as a philological discipline. Then I discuss the structural, methodological and ideological problems that made it difficult to follow Dumont’s advice to search for the point of confluence of sociology and Indology. Finally, I place Dumont’s holistic approach in relation to the holistic structure of academic disciplines that emerged in the 19th century on the basis of the nation-state model and argue that it is misleading and reductive to think that ‘the construction of an Indian Sociology rests in part upon the existence of Indology’.